Early Impacts of College, Interrupted: Considering First-Year Students' Narratives About COVID and Reports of Adjustment During College Shutdowns. (November 2022) - Booker, Jordan A.; Ell, Mikayla; Fivush, Robyn; Greenhoot, Andrea Follmer; McLean, Kate C.; Wainryb, Cecilia; Pasupathi, Monisha
The COVID-19 pandemic has threatened lives and livelihoods, imperiled families and communities, and disrupted developmental milestones globally. Among the critical developmental disruptions experienced is the transition to college, which is common and foundational for personal and social exploration. During college shutdowns (spring 2020), we recruited 633 first-year U.S. students (mean age = 18.83 years, 71.3% cisgender women) to provide narratives about the impacts of the pandemic. We tested the ways narrative features were associated with concurrent and longitudinal COVID stressors, psychosocial adjustment, and identity development. Narrative growth expressed in spring 2020 was positively associated with psychosocial adjustment and global identity development and was negatively associated with mental health concerns. Associations were supported concurrently and at 1-year follow-up. Growth partly explained associations between COVID stressors and students' adjustment. Our findings reinforce the importance of growth for resilience and underscore the importance of connective reasoning as people navigate a chronic stress.